MULTI PURPOSE AGRICULTURAL TRUCK. - Albert Francis A & Gowtham K2 (International Journal of Research Science and Management, 2017)
The design of carrier unit of the existing tippers must be modified to facilitate the collection of loads from the tippers into pockets or bags. The dropping of loads from a tipper can be done only at the rear side of the vehicle, it is to be modified to meet the requirements of dropping the loads on sides of the vehicle. While changing the direction of discharge from tippers the equilibrium of the vehicle must be considered to maintain the stability of the vehicle. So it requires special arrangements to maintain the equilibrium of the vehicle. Special vehicles are used to load heavy particles into the tippers, to increase the efficiency and to decrease the process cost a machine is to be attached with the vehicle to perform the loading operation..